2011
DOI: 10.1007/s00431-011-1442-5
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus obstructing the right ventricle outflow tract in a neonate with methylenetetrahydrofolate reductase 677TT genotype

Abstract: At her first day of life, a neonate presented with severe cyanosis and a mass obstructing the right ventricle outflow tract. Prostagladin E1 was necessary to provide pulmonary blood flow. The mass was removed using extracorporeal bypass surgery; the right ventricle was dilated, and the pulmonary valve leaflets were damaged. Sternal closure was delayed because of bleeding and poor cardiac performance. Histology demonstrated that the mass was a mixed thrombus. Investigation revealed homozygous 677TT genotype of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Dear Sir, We read with great interest the recent case report by Kovacikova et al [3] who demonstrated a thrombus obstructing the right ventricle outflow tract in a neonate with methylenetetrahydrofolate reductase (MTHFR) 677TT genotype. The authors stated that a thrombus in a neonate could be a result of a combination of acquired and congenital thrombogenic risk factors, and a mutation analysis should be performed.…”
mentioning
confidence: 99%
“…Dear Sir, We read with great interest the recent case report by Kovacikova et al [3] who demonstrated a thrombus obstructing the right ventricle outflow tract in a neonate with methylenetetrahydrofolate reductase (MTHFR) 677TT genotype. The authors stated that a thrombus in a neonate could be a result of a combination of acquired and congenital thrombogenic risk factors, and a mutation analysis should be performed.…”
mentioning
confidence: 99%
“…We appreciate the interest of Dr. Demirel and associates in our article describing a thrombus obstructing the right ventricle outflow tract in a neonate with 677TT methylenetetrahydrofolate reductase genotype [6]. In this case, surgical thrombectomy was used as a method of choice for the treatment of a life-threatening thrombosis.…”
mentioning
confidence: 99%